Lignin - Chemistry, Structure, and Application 2023
DOI: 10.5772/intechopen.108263
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Potential of Lignin Valorization with Emphasis on Bioepoxy Production

Abstract: Lignin is the second most abundant natural polymer after cellulose. It has high molecular weight and poor dispersity, which lowers its compatibility with other polymeric materials. Accordingly, it is hard to integrate lignin into polymer-based applications in its native form. Recently, lignin valorization, which aims to boost lignin value and reactivity with other materials, has captured the interest of many researchers. The volatility of oil and gas prices is one strong incentive for them to consider lignin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Nevertheless, agro-residues are considered as lignocellulosic biomass and consist mainly of cellulose, hemicelluloses, lignin, besides other organic matters [ 2 , 3 ]. Currently, considerable works [ [4] , [5] , [6] ][ 7 ] have been conducted on agro-residues for reducing the risks associated with their disposal, and to promote their use in biofuels, construction, polysaccharide productions, and animal feed. Also, it was found that pyrolysis of these biomasses can yield biochar, bio-oil and bio-diesel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, agro-residues are considered as lignocellulosic biomass and consist mainly of cellulose, hemicelluloses, lignin, besides other organic matters [ 2 , 3 ]. Currently, considerable works [ [4] , [5] , [6] ][ 7 ] have been conducted on agro-residues for reducing the risks associated with their disposal, and to promote their use in biofuels, construction, polysaccharide productions, and animal feed. Also, it was found that pyrolysis of these biomasses can yield biochar, bio-oil and bio-diesel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%